Designing Debt Payment Standard Operating Procedures in the SMEs Retail Industry Using Business Process Modeling and Notation (BPMN): A Case Study of a Retailer in East Java, Indonesia - Sulthan, Nafis Sulthan; Jaswadi, Jaswadi; Sulistiono, Sugeng (Dinasti International Journal of Economics, Finance & Accounting, 2021)
The application of standard operating procedures on the micro, small, and medium enterprise retail industry was critical since this type of enterprise employs the majority of national workforces and has become the most significant sector in Indonesia's economic growth. The purpose of this study was to investigate the business process and develop standard operating procedures for the debt payment process at one of the representative retailers in East Java Province, Indonesia, PO Dolopo Grosir. This study was part of a descriptive and qualitative study. Interviews and observations were also used to obtain data. According to the research, the development of a business process diagram would be the standard operating procedure during the debt payment process. Business Process Modeling develops this SOP creation activity further by adding several related artifacts such as data and business rules. The business process model modeled with BPMN can be used by parties who understand technical matters to be translated into information system needs.